2001
DOI: 10.1209/epl/i2001-00373-4
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic thermodynamics of equilibrium characterized by power law canonical distributions

Abstract: Macroscopic thermodynamics of equilibrium is constructed for systems obeying power law canonical distributions. With this, the connection between macroscopic thermodynamics and microscopic statistical thermodynamics is generalized. This is complementary to the Gibbs theorem for the celebrated exponential canonical distributions of systems in contact with the heat bath. Thereby, a thermodynamic basis is provided for power law phenomena ubiquitous in nature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…The convolution of these distributions was shown to converge to the limiting Lévy distribution [30], according to the Lévy-Gnedenko generalized central-limit theorem [31]. Furthermore, the interrelationship between microscopic statistical and macroscopic thermal equilibria for such power-law systems was shown to be a natural extension of the corresponding Boltzmann-Gibbs theory [32].…”
Section: Applications To Special Functions Used In Statisticsmentioning
confidence: 99%
“…The convolution of these distributions was shown to converge to the limiting Lévy distribution [30], according to the Lévy-Gnedenko generalized central-limit theorem [31]. Furthermore, the interrelationship between microscopic statistical and macroscopic thermal equilibria for such power-law systems was shown to be a natural extension of the corresponding Boltzmann-Gibbs theory [32].…”
Section: Applications To Special Functions Used In Statisticsmentioning
confidence: 99%
“…This is in fact the original and most frequently invoked motivation of the formulation and, consequently, constitutes its genuine source of validation. Our results clarify whether Tsallis's statistics is relevant to an aspect that-in spite of its essential role in thermodynamics-has been scarcely treated in the profuse literature on Tsallis's theory [16], namely, thermal equilibrium between interacting systems. Assume to have a system which, due to its nonextensive nature, exhibits an energy distribution of the form of Eq.…”
mentioning
confidence: 61%
“…The value of the parameters in the thermometer distribution predicted by Tsallis's formalism, however, results to be wrong. Abe and Rajagopal [16] have shown that a formal extension of equilibrium conditions for two systems in thermal contact yields, in Tsallis's theory, β q = β q ′ , where q and q ′ are the nonextensivity indices corresponding to the two systems [17]. Our results show that this relation is generally not satisfied.…”
mentioning
confidence: 69%
“…We use the relation (12) in finding the most probable partition of energy in conformity with the principle of equal a priori probability. We find that the two attain the same "temperature" β β Consider as before the case when S 1 is a small system immersed in the very large heat bath (reservoir) S 2 .…”
Section: -Amentioning
confidence: 99%
“…(2') This is the new factor in place of the Boltzmann factor [12]. As before, this derivation is based entirely on macroscopic considerations and probability concepts.…”
Section: -Amentioning
confidence: 99%